86.7k views
4 votes
Can somebody please explain how to do this?

Can somebody please explain how to do this?-example-1
User AdPartage
by
5.3k points

2 Answers

3 votes

x = -24 + y/2

y = 8x

I hope this helped :)

User Abalta
by
4.9k points
3 votes
As we already have the value of y,we can put it into another equation.

Here's how we can solve the equation:

y = 2x+48...(1)
y = 8x...(2)

Put (2) into (1)

(8x) = 2x+48
8x-2x = 48
6x = 48
x = 8...(3)

Put (3) into (1)
y = 8(8)
y = 64

Thus, x=8, y+64

Hope it helps!
User Charles Mager
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.